Audacity: Learning Media Design in Listening Skills for Arabic Special Development Program - Fikri, Shofil; Kirom, Makhi Ulil; Al-Furqaan, Dimas Luqman (Jurnal Internasional Pendidikan Bahasa Arab, 2024)
Audacity is an application that is easy to apply and efficient in making it easier for educators to design listening skill lessons. Therefore, this research aimed to test the effectiveness of the listening skill learning media design using Audacity in the Special Arabic Language Development Program (PKPBA) in Maulana Malik Ibrahim State Islamic University, Malang. Researchers applied quantitative research methods. And based on data collection techniques, this research was classified as experimental research, namely a pre-experimental design by comparing one group pre-test and post-test. The pre-test and post-test applied by researchers was by giving a number of listening skill tests regarding professions. The data obtained was then analyzed using quantitative descriptive techniques with the help of IBM SPSS Statistics 26 in the paired samples test. The results of this research are: First, to be able to use the latest version of the Audacity (Audacity 3.3.2), with quality audio results that are easy for students to digest, you need to set several important features including: 1) Noise Redaction, 2) Normalize, 3) Compressor, 4) Filter Curve. Second, based on the results of the pre-test and post-test, the average difference between the two, namely 14.3. So, from these results that the use of the Audacity application is very effective for learning listening skills at PKPBA. Therefore, the novelty of this research is, learning Arabic by designing learning media using the Audacity very effective for improving students' listening skills in learning Arabic.